Strategi Pengasuh Dalam Pembentukan Karakter Filantropis di Panti Asuhan Putra Muhammadiyah Probolinggo - Ardli, Muhammad Nabat; Reza Hilmy Luayyin; Romli, Ahmad Syaifuddin (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research is a field research aimed at knowing and understanding the role and strategy of caregivers in shaping philanthropic characters in the foster children of Muhammadiyah Probolinggo orphanage. This study uses a qualitative descriptive approach with a type of field study research that takes place naturally in the original environment of the research object (natural setting). The results of the study show that the role of caregivers in the formation of philanthropic character in foster children in the Muhammadiyah Putra Orphanage in Probolinggo City is achieved through several holistic and integrated approaches in the role, including 1) the caregiver as the caregiver itself and also the caregiver as a companion as well as a parent so that they can have emotional, psychological, empathetic and social closeness. 2) The strategy of caregivers in shaping philanthropic character in Muhammadiyah boys' orphanages is to provide several programs and activities called role simulations, emotional reflections, volunteer days, and support for friends. 3) Challenges faced by caregivers in the formation of philanthropic character in Muhammadiyah orphanage foster children include psychological, social, and cultural challenges. The psychological challenges obtained are in the form of the mentality of the recipients of assistance, and the social challenges obtained are in the form of age differences in foster children, while cultural challenges are in the form of the backgrounds of foster children who come from rural communities that also lack proper education.